Molecular Hydrogen Positively Affects Physical and Respiratory Function in Acute Post-COVID-19 Patients: A New Perspective in Rehabilitation - Botek, Michal; Krejčí, Jakub; Valenta, Michal; McKune, Andrew; Sládečková, Barbora; Konečný, Petr; Klimešová, Iva; Pastucha, Dalibor (International journal of environmental research and public health, 2022)
Molecular hydrogen (H2) is potentially a novel therapeutic gas for acute post-coronavirus disease 2019 (COVID-19) patients because it has antioxidative, anti-inflammatory, anti-apoptosis, and antifatigue properties. The aim of this study was to determine the effect of 14 days of H2 inhalation on the respiratory and physical fitness status of acute post-COVID-19 patients. This randomized, single-blind, placebo-controlled study included 26 males (44 ± 17 years) and 24 females (38 ± 12 years), who performed a 6-min walking test (6 MWT) and pulmonary function test, specifically forced vital capacity (FVC) and expiratory volume in the first second (FEV1). Symptomatic participants were recruited between 21 and 33 days after a positive polymerase chain reaction test. The experiment consisted of H2/placebo inhalation, 2 × 60 min/day for 14 days. Results showed that H2 therapy, compared with placebo, significantly increased 6 MWT distance by 64 ± 39 m, FVC by 0.19 ± 0.24 L, and, in FEV1, by 0.11 ± 0.28 L (all p ≤ 0.025). In conclusion, H2 inhalation had beneficial health effects in terms of improved physical and respiratory function in acute post-COVID-19 patients. Therefore, H2 inhalation may represent a safe, effective approach for accelerating early function restoration in post-COVID-19 patients.
Keywords: Forced Expiratory Volume; Single-Blind Method; Respiratory Function Tests; lidé; Female; jednoduchá slepá metoda; mužské pohlaví; respirační funkční testy; vodík; SARS-CoV-2; Hydrogen; Male; usilovný výdechový objem; COVID-19; ženské pohlaví; Humans